Professorial lecture UiTM: nurturing the intellectual mind: the story of mathematics and technology / Parmjit Singh - Singh, Parmjit (UiTM Press, 2019)
There are a number of pervasive myths about mathematics learning and the usage of technology in current classroom practices in enhancing students' intellectual mind. These different myths often hinders the learning and intellectual growth of the students significantly. There is a widespread agreement that mathematics should be taught as a thinking activity. However, the quality of this mathematical knowledge in relation to college students' mathematical thinking development at present times must be identified. Secondly, it is evident that the assimilation of technology in societal domains has crucially impacted the daily lives of society at large. However, the question remains as to this flip side of the coin with regards to this assimilation, particularly in relation to classroom pedagogical practices at Higher Education Institution (HEI).